STUDYING OF PROBABILITY DISTRIBUTION TYPES OF FATIGUE FAILURE FOR GH4133 DISC MATERIALS - WAN HongQiang; GAO Gang; DING Feng (Jixie qiangdu)
Studying of probability distribution types of fatigue failure for GH4133 disc material,through the empirical distribution function and the average failure rate function methods to deal with the fatigue failure data. Based on the obtained data information,hypothesizing disk material fatigue failure probability distribution is the normal distribution, the lognormal distribution or the three parameter Weibull distribution. By means of parameter estimation for the three distributions,then using the Kolmogorov test of goodness fit method,to test the overall fitting effect of this distribution function. And to plot failure rate curves which distribution has been determined compare with the average failure rate curves. Comparing the data of each group which is under the same temperature with different strain ratio and the same stain ratio with different temperature then come to conclusion that the lognormal distribution is best fatigue failure distribution function for GH4133 disk material.